Consequences of urban migration of adult children for the elderly left-behind in rural Vietnam - Nguyen, Thi Thu Hien (Curtin University, 2019)
Following market liberalisation in Vietnam, concern has been raised about the elderly ‘left behind’ by the urban migration of adult children from rural areas. This study used qualitative methods to examine the consequences for these elderly and the strategies they adopt to cope. It found overall positive outcomes for rural aged parents with migrant children, as long as at least one family member remained nearby. However, elderly with no remaining family members suffered more.